Consumer Demographics and Environmental Responsibility: An Empirical Investigation of the Consumers in Tripura - Das, Manish (Prabandhan: Indian Journal of Management, 2015)
This research paper aimed to explore the environmental responsibility of the consumers of Tripura and its significance with various demographic variables. The total sample size selected for the study were 224 respondents, and the sampling method was simple random sampling. ECOSCALE (Stone et al. 1995) was used to collect data from the samples. The reliability of the scale was measured to find out the appropriateness of the scale to measure environmental responsibility of the consumers of Tripura. The collected data were analyzed by using statistical software SPSS v17.0. Factor Analysis for all the seven components of the ECOSCALE was carried out to obtain the factor scores, which were used for measuring the significance of the ECOSCALE dimensions among the various demographic groups. Independent sample ’t’ test and one-way ANOVA were used to measure the significance. The data analysis revealed that the older consumers exhibited greater responsibility towards the environment than the younger people; married consumers were more environmentally responsible than the unmarried consumers; consumers engaged with private organizations were more responsible towards the environment rather than people engaged in other occupations;Â and consumers with moderate earnings were more responsible towards the environment than consumers with more earnings. Education had a partial significance, while gender of the consumers did not have any significant relation with environmental responsibility of the consumers of Tripura.